GOOD TOUCH, BAD TOUCH: IMPLEMENTING LIFT-THE-FLAP BOOK TO ENHANCE EARLY SEXUAL EDUCATION FOR CHILDREN - Siti Fitriana; Ellya Rakhmawati; Suhendri Suhendri; Wiwik Kusdaryani (PEDAGOGIK : JURNAL PENDIDIKAN, 2026)
The lack of an appropriate approach in delivering early sexuality education results in children not fully understanding body boundaries and safe and unsafe forms of touch. This condition increases children's vulnerability to potential sexual violence, requiring developmentally appropriate learning strategies. This study aims to examine the implementation of lift-the-flap books in improving children's understanding of the concepts of good and bad touch, while simultaneously encouraging active engagement in the learning process. This study used a descriptive qualitative approach with 25 children aged 4–6 years as subjects. Data were collected through participant observation and semi-structured interviews, then analyzed using thematic analysis techniques. The results showed that the use of lift-the-flap books can improve children's understanding of body boundaries in a more concrete way and encourage active engagement through interactive and fun exploratory activities. Furthermore, this media also helps children express their understanding more openly. These findings confirm that the integration of interactive media in learning not only strengthens cognitive aspects but also creates meaningful, contextual learning experiences that are responsive to the developmental needs of early childhood.